#CoveringClimateNow: A social journalism project profiling climate and health. (30th September 2020) - Williams, M; Sweet, M; McInerney, M; Finlay, S
Abstract: Concerns about poor quality media reporting of climate change has led to many initiatives seeking to influence coverage. In 2019/2020, a global media collaboration was established with the aim of generating a sustained media focus on key climate-related events. This paper reports an analysis of an Australian health media organisation's contribution to the collaboration, and the opportunities this provided for public health advocates, Aboriginal and Torres Strait Islander researchers and communities, and the wider community. It presents key reflections from Croakey Health Media's contribution to the global #CoveringClimateNow collaboration, with the aim of providing practical advice to enable further such collaborations and activities in other countries. This project was run on a very small budget, and this presentation is likely to be particularly relevant for low-budget organisations and contexts. Key messages: Poor quality media coverage of climate change has stimulated innovation. Collaboration locally and globally can convey solutions to climate change.